The Rights of the Palestinian Woman between Sharia and Its Application in the Palestinian constitution - Totah, Sanaa Maher (Journal of Ecohumanism, 2025)
The Islamic religion is interested in regulating woman's rights and respecting her dignity, where Islam divided woman's rights into public rights and political rights. Indeed, this is evident in the current study entitled "The rights of the Palestinian woman between Sharia and its application in the amended Palestinian constitution of 2005". There is a variation among the international documents related to woman's rights from one county to another based on the political and social conditions of countries; accordingly, the Palestinian constitution approved the rights and freedoms of the Palestinian woman in accordance with the social and political context. Despite the superiority of constitution over all the regular legislations, we can see that the regular laws varied in terms of protection of woman's rights, as stated in the Jordanian penal law of 1960, which is applied in Palestine and the personal status law of 1976, which will be addressed in this study.